PENGELOLAAN LABORATORIUM FISIKA SMA DI KOTA SAMARINDA PADA ERA DIGITAL - Jimmy Hendrawan; Sitti Nurfaika; Novia Rahmadayanti; Zulaika Ramadhani; Rahman Setiyawan; Nurul Fitriyah Sulaeman (Universitas Jember, 2022)
The problem in this study is how to manage the physics laboratory at A Samarinda Senior High School and B Samarinda Senior High School. The purpose of this study was to find out and describe the management of physics laboratories in A Samarinda Senior High School and B Samarinda High School. This study used descriptive research with data collection techniques carried out by means of documentation and interviews. The results of this study generally concluded that the management of physics laboratories at A Samarinda Senior High School and B Samarinda High School is quite good and supports physics learning. This can be seen from the laboratory planning that has been carried out optimally even though there are still many limitations, the implementation of the planning has been done well.